Anticancer Activity of Ether Derivatives of Chrysin - Arkadiusz Sokal; Patryk Mruczek; Mateusz Niedoba; Agnieszka Dewalska; Klaudia Stocerz; Monika Kadela-Tomanek (Molecules)
Chrysin, a naturally occurring flavonoid, exhibits a broad spectrum of biological activities, including showing anticancer properties. However, its clinical application is limited by poor bioavailability and low solubility. The introduction of an amine, amide, ester, or alkoxy group to a flavone skeleton influences the biological activity. This review also discusses hybrid compounds, such as the chrysin–porphyrin hybrid, which are characterized by higher biological activity and better bioavailability properties than single molecules. This review concentrates on the anticancer activity of chrysin and its derivatives against the most popular cancers, such as breast, lung, prostate, and gastrointestinal tumors.